(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2025)
Adult butterflies lay their eggs on specific plants that serve as the primary food source for caterpillars once they hatch. This study, conducted from March 2023 to April 2025, aimed to develop a comprehensive checklist and evaluate the distribution of butterfly species in Kaptai National Park (KNP), Bangladesh. A total of 103 plant species from 41 families were identified as larval host plants for 87 butterfly species belonging to 9 families. Of these plant species, 17 were classified as Least Concern (LC) according to the IUCN Red List 2024 for Bangladesh, while 86 species remain unclassified. The study covered eight sites (S1-S8) in Ram Pahar and Sita Pahar within KNP, emphasizing the distribution of 26 important larval host plant species that are ecologically significant and commonly utilized by butterflies. The 26 key plants include Syzygium cumini, Mangifera indica, Anacardium occidentale, Annona squamosa, Alstonia scholaris, Calotropis gigantea, Aristolochia indica, Mikania micrantha, Terminalia catappa, Delonix regia, Butea monosperma, Saraca asoca, Mimosa pudica, Tamarindus indica, Senna alata, Lagerstroemia speciosa, Bombax ceiba, Abelmoschus manihot, Ficus benghalensis, Moringa oleifera, Jasminum auriculatum, Passiflora foetida, Neolamarckia cadamba, Citrus aurantiifolia, Mimusops elengi, and Curcuma longa. These findings underscore the urgency of protecting butterfly habitats, including native plant species. The study also highlights the importance of habitat restoration and sustainable conservation initiatives in the Chittagong Hill Tracts area. Asian Australas. J. Biosci. Biotechnol. 2025, 10(3), 77-92